Development of a grain-milk functional beverage and evaluation of physico-chemical and sensory properties - Wickramarachchi, L.A.; Herath, H.M.T.; Rajawardene, D.U.; Jayasinghe, M. (University of Jaffna, 2022)
Consumer demand for functional foods is an increasing trend in the new century. The aim of this study was to develop a low-fat gluten-free functional multi-grain beverage by improving nutritional and flavor profiles. In the present study, a grain-based milk beverage was newly developed from grain extract, which was prepared by mixing selected grains at pre-determined grain ratios (sorghum: horse gram: red rice ‘kuruluthuda’; 5:2:3 respectively) followed by soaking overnight, pressure cooking and blending with water (1:3). Formulation of grain-milk beverages were performed in three grain extract ratios (60 %, 65 % and 70 %) with cow’s milk, sesame milk, sweetener (Kithul treacle and sugar) and carrageenan followed by homogenizing and sterilizing at 121 ℃ for 15 min. The best formulations were selected as 70 % multi-grain extract, 15 % cow’s milk, 8 % sesame milk, 7 % sugar and 70 % multi-grain extract, 15 % cow’s milk, 5 % sesame milk, 10 % treacle while carrageenan as a stabilizer (0.1 %) based on the sensorial attributes. The total soluble solid, total acidity and pH of the beverage with sugar and treacle were (12.13±0.06 %, 12.10±0.1 %), (0.01±0.001 %, 0.02±0.001 %) and (6.11±0.01, 5.8±0.001) respectively. The chemical properties of fat, protein, crude fiber, total ash, carbohydrate, total sugar, and caloric value of grain-milk beverage containing sugar and treacle were (1.46±0.02 %, 1.03±0.01 %), (1.46±0.12 %, 1.46±0.10 %), (0.78±0.13 %, 0.82±0.01 %), (0.37±0.01 %, 0.37±0.01 %), (11.66±0.01 %, 11.70±0.01 %), (9.43±0.001 %, 9.45±0.001 %), and (66.06 Kcal, 65.41 Kcal) respectively. The mineral contents of grain-milk beverages containing sugar had Na (21.30 mg/100 mL), K (76.00 mg/100 mL), Ca (2.64 mg/100 mL) and Mg (15.56 mg/100 mL) while grain-milk beverages containing treacle had Na (14.90 mg/100 mL), K (74.80 mg/100 mL), Ca (2.41 mg/100 mL) and Mg (13.76 mg/100 mL) respectively. Vitamins B1, B2, B3, B6, B9, and E were not found, but Vitamin B5 levels were 1.9 mg/100 g and 2.1 mg/100 g, respectively. The developed beverages had acceptable organoleptic properties with high potential to be introduced as healthy functional beverages.
Keywords: Sorghum; Horsegram; Red Rice; Grain-milk beverage; Functional beverage